Fritz K. Oser ve dini gelişim teorisi - Albayrak, İzzet (My University, 2020)
Bu araştırmada, Fritz K. Oser’ın dini yargı teorisine dair görüşleri incelenmeye ve yorumlanmaya çalışılmıştır. Oser, dini gelişimin ‘dini yargı’ denilen yönü üzerine odaklanmıştır. Teorisinde, zihinsel gelişim ile dini yargıya yönelik bütüncü bir bakış açısı ortaya koymaktadır. Gelişim evrelerinin, insanların Tanrı’ya ilişkin kişisel tecrübelerinden hareketle aktardıklarından yola çıkarak farklılaşacağını söylemektedir. Araştırması sonucunda dini yargı gelişimini 5 farklı evrede açıklar. Bu evreler boyunca insanın, gelişen bir bağımsızlık ihtiyacından bahseder ve Tanrı inancının bu şekilde değişime uğradığını söyler.Bir giriş ve iki bölümden oluşan bu tezin giriş bölümü araştırmanın konusundan, amacından ve öneminden bahseder. İkinci bölümü, yani Oser’ın dini gelişim teorisini anlayabilmek adına din, gelişim, evre, dini yargı, dini anayapı gibi kavramlar; dini yargının gelişimi üzerine önceki araştırmalar gibi konulara yer verilmektedir. Üçüncü bölüm Fritz Oser’ın hayatını genel hatlarıyla içermektedir. Çalışmalarından bazıları sunulmuştur. Çalışmanın temel konusu olan Oser’ın dini yargı gelişimine dair görüşleri, beş evre olarak belirlediği kuramı bir araya getirilmiş ve yorumlanmıştır.

In this research, Fritz K. Oser’s views on the theory of religious judgement have been tried to analyzed and interpreted. Oser focused on the aspect of the religious improvement named ‘religious judgment’. In his theory, he puts forward a holistic perspective on the mental development and religious judgment. He says that the stages of development will differ in terms of what people tell about their personal experiences which are God based. As a result of his research, he explains the development of religious judgment in 5 different stages. During these phases, he mentions a human’s need for independence and he says that belief in God undergoes changes in this way.The introduction part of this thesis, which consists of an introduction and two parts, mentions the subject, purpose and the importune of the research. İn order to understand Oser’s religious development theory, concepts such as religion, development, stage, religious judgment, religious foundation; topics such as previous research on the development of the religious judiciary are included in the second part. In the third section includes Fritz Oser’s life as an outline –some of his works are presented-. Oser’s views on the development of religious jurisdictions, which is the main subject of the study, and the theory that he determined as five stages were brought together and interpreted.
Keywords: Ana-yapı; Din; Dini Gelişim; Dini yargı; Evreler; F. Oser; Felsefe ve din; Fritz Oser Religion; Mother-structure; Philosophy and religion; Psikoloji; Psychology; Religion; Religious Development; Religious judgment; Stages